Analysis of Attribute Control Chart in Rubber Roller Production Process at PT Nesinak Industries - Andika Kuswara; Dene Herwanto (School of Industrial and System Engineering, Telkom University, 2022)
PT Nesinak Industries is a manufacturing company that produces rubber parts products. One of its productsis a rubber roller for printers. During the production process, several types of defects were found. In theperiod 2018 – 2020, there is a 1.7% defect in total production. Of course, there is a gap between the actualconditions and the company‘s expectations to reduce the level of defects to zero. For this reason, it isnecessary to carry out quality control to reduce the level of defects. In this study, attribute control chartsare used as a quality control tool based on the number of defects that occur in rubber roller products. Inaddition, to find out the dominant defects and the focus of improvement, the pareto diagram can be used.Furthermore, with a fishbone diagram can be known the causes of defects. The dominant type of defect isfound in the type of hole defect. Based on the results of the attribute control chart, in the rubber rollerproduction process, several are not under control and need to be repaired. Furthermore, the factors thatcause the product to have defects are human, machine, method, and material.